Societal Alienation Analysis in Chuck Palahniuk Novel “Fight Club” - Razak, Muhammad Fauzi; Riskiawati, Nur Sapta (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2024)
This study examines the types of societal alienation displayed through main character in the 1996 novel "Fight Club" written by Chuck Palahniuk. The novel follows the story of Jack, an insomniac who forms a fight club with Tyler Durden, a charismatic and mysterious figure. The study employs a qualitative analysis of the novel’s narrative and characters to explore how societal alienation is portrayed and its impact on the main characters. The data consists of primary and supporting data. The researcher collected data through watching and reading the movie and movie transcript thoroughly. The researcher used sociological theory, and identifying relevant issues that align with the research questions. The researcher also utilized a qualitative research design and employed document or content analysis as the research method. Based on the research results some societal alienation types are portrayed by the main character such as self-isolation, estrangement, and normlessness.